Dose–response characteristics of noninvasive ventilation in acute respiratory failure. Issue 1 (10th January 2020) - Hukins, Craig; Murphy, Michelle; Edwards, Timothy
Acute noninvasive ventilation (NIV) is a well-established therapy for acute respiratory failure but the dose–response characteristics of this therapy have not been defined. The aim of this study was to define this dose–response relationship. This study was a retrospective review of patients receiving NIV for acute respiratory failure in a tertiary hospital respiratory high-dependency unit between July 2012 and June 2017. Mask-on time (rather than the period that NIV was in use) as the "dose" was compared with hospital survival as the "response". 654 patients were included, 594 (91%) with hypercapnic respiratory failure (HCRF). NIV was used for a median (interquartile range (IQR)) duration of 2.74 (1.51–4.73) days and median (IQR) mask-on time was 34 (18–60) h (56.1% (41.2–69.5%) of treatment time). There was evidence of a dose–response relationship in the HCRF group up to a ceiling of 24 h mask-on time, but not in the hypoxaemic respiratory failure (HRF) group. There was a difference in survival with as little as 2 h mask-on time (92% compared with 73%; p<0.001). Patients requiring NIV for 80–100% of therapy time had lower survival. We conclude that there is evidence of a dose–response relationship between cumulative NIV usage (mask-on time) and survival from as little as 2 h to a ceiling of ∼24 h in HCRF, but not in HRF. Acute NIV in respiratory failure has a dose–response effect on survival from as little as 2 h of therapy http://bit.ly/2okErQZ